2015
DOI: 10.1186/s12876-015-0354-7
|View full text |Cite
|
Sign up to set email alerts
|

Trans-anal irrigation therapy to treat adult chronic functional constipation: systematic review and meta-analysis

Abstract: BackgroundTrans-anal irrigation (TAI) is used widely to treat bowel dysfunction, although evidence for its use in adult chronic functional constipation remains unclear. Long-term outcome data are lacking, and the effectiveness of therapy in this patient group is not definitively known.MethodsEvidence for effectiveness and safety was reviewed and the quality of studies was assessed. Primary research articles of patients with chronic functional constipation, treated with TAI as outpatients and published in Engli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 23 publications
1
15
0
2
Order By: Relevance
“…Transanal irrigation using commercially available kits is being increasingly used for the management of bowel dysfunction, including FC. A systematic review and meta‐analysis of the available uncontrolled studies in FC suggested a 50% response rate, which is comparable to that obtained with pharmacological agents . Theoretically, this technique could lead to perforation, but a separate study addressing this possibility has suggested this risk is very low .…”
Section: Resultsmentioning
confidence: 78%
“…Transanal irrigation using commercially available kits is being increasingly used for the management of bowel dysfunction, including FC. A systematic review and meta‐analysis of the available uncontrolled studies in FC suggested a 50% response rate, which is comparable to that obtained with pharmacological agents . Theoretically, this technique could lead to perforation, but a separate study addressing this possibility has suggested this risk is very low .…”
Section: Resultsmentioning
confidence: 78%
“…Studies on adults with defecation disorders of mixed etiology have reported variable response rates to TAI[ 5 ]. The proportion of patients with a positive outcome with TAI ranges from 30%[ 16 ] to 78%[ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…TAI was first introduced into clinical practice by Shandling and Gilmour for children with neurogenic bowel dysfunction (NBD) related to spina bifida[ 3 ]. Based on its clinical efficacy in treating children with NBD, TAI was then applied to adults with NBD[ 4 ] and to children and adults with functional bowel disorders for whom traditional treatments had failed[ 5 ]. While short-term trials indicated that constipation and FI are significantly improved by TAI, compliance is difficult to maintain over time[ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with refractory constipation (unresponsive to various therapeutic options) can respond to trans-anal irrigation, which involves the introduction of water (70-1,000 mL) into the rectum and sigmoid colon. The response rates are significant (30-65%), so this can be used effectively as a conservative option before considering invasive treatments (Emmett, Close, Yiannakou, & Mason, 2015;Wilkinson-Smith et al, 2018). Indeed, surgery is a last resort and is reserved for only a small number of unresponsive patients, as it can cause more harm than good and will not guarantee restoration of neuromuscular function (Wilkinson-Smith et al, 2018).…”
Section: Defecatory Disordermentioning
confidence: 99%